Penerapan Metode Pembelajaran The Power Of Two Untuk Meningkatkan Pemahaman Belajar Siswa Dalam Pelajaran Pendidikan Agama Islam Pada Siswa Kelas VII SMP IT Humayya Berandan Barat - Tiara Amelia, M. Yusuf Abdullah, Usmaidar (Pusdikra Publishing, 2023)
Efforts to improve learning outcomes for class VII students of SMP IT Humayya Berandan Barat in the Islamic Religious Education subject matter of faith in Allah and wisdom is carried out by applying the power of two learning strategy with two cycles and showing an increase in student learning outcomes. The application of the power of two learning strategy is carried out in Islamic Religious Education lessons in class VII SMP IT Humayya Berandan Barat by implementing it according to the plan that has been made, learning activities are carried out by starting with giving pretests to students, then forming study groups by dividing material to each each group. The next step is still in the teacher's guide in the form of class percentage actions and group work carried out by students and ends with giving conclusions and a post test. Efforts to improve learning outcomes for class VII students of SMP IT Humayya Berandan Barat in the Islamic Religious Education subject matter of faith in Allah and His wisdom after applying the The power of two learning method in cycle I the average value increased to 85 with a completeness percentage of 77% and the percentage mastery learning has not reached 85%. And cycle II the average score of students reached 94 (30 students) with a completeness percentage of 100% with an increase in the difference from cycle I to cycle II of 41%. Thus cycle II experienced a significant increase, so the researcher concluded that there was no need to continue in the next cycle.